Respuesta :

Answer:

-5, 3/2

Step-by-step explanation:

Use the factoring method to solve for the roots.

2x^2 + 7x - 15 = 0

(x+5)(2x-3) = 0

x + 5 = 0

x = -5

2x - 3 = 0

2x = 3

x = 3/2

Answer:  [tex]\bold{a)\quad \bigg(-5,\dfrac{3}{2}\bigg)}[/tex]

Step-by-step explanation:

[tex]2x^2+7x-15=0\\\\2(-15)=-30\implies -3\ and\ 10\ \text{have a product of -30 and sum of 7}\\\text{So the quadratic equation is factorable.}\\\text{Use the Grouping Method (replace 7x with 10x and -3x):}\\\\2x^2+10x\quad -3x-15=0\\2x(x+5)\quad -3(x+5)\ =0\\(2x-3)\qquad (x+5)=0\\2x-3=0\qquad and\qquad x+5=0\\\large\boxed{x=\dfrac{3}{2}}\qquad and\qquad \large\boxed{x=-5}[/tex]